Nonketotic hyperglycemia: The culprit behind refractory seizures in a case of traumatic brain injury - Manappallil, Robin George; Supreeth, Ramesh Naga (Asian Journal of Medical Sciences, 2017)
Asian Journal of Medical Sciences Vol.8(2) 2017 101-102